Out of the Past: A Case Report of Left Ventricle Free Wall Rupture - Kattamuri, Lakshmi; Sharma, Kunal; Kahtan, Fadah; Rajachandran, Manu (International Journal of Angiology, 2025)
Left ventricular free wall rupture (LVFWR) is a now exceedingly rare, but potentially life-threatening complication of myocardial infarction (MI) that can present as cardiac tamponade and/or cardiogenic shock. Seen more commonly in days prior to reperfusion as a sequela of complicated transmural MI, LVFWR has seen a decline in incidence in the age of primary angioplasty for MI. It is now a rarely encountered phenomenon usually associated with late-presenting MI. We present a case of LVFWR following a late-presenting MI with severe shock and cardiac tamponade. Initial transthoracic echocardiography with contrast showed pericardial effusion with cardiac tamponade and no overt signs of rupture. Computed tomography angiography of the chest and Transesophageal echocardiography did not demonstrate aortic dissection. Pericardiocentesis of hemorrhagic effusion transiently improved hemodynamics but was followed by rapid cardiac decline and death. Subsequent necropsy showed left ventricular wall rupture with focal fibrosis in the distal left ventricular wall, consistent with a remote infarction, along with a large pericardial clot. This case underscores the diagnostic challenges of LVFWR, particularly when imaging is inconclusive in hemodynamically unstable patients. Despite technological advances, clinical suspicion remains paramount, especially in patients presenting with shock and hemorrhagic pericardial effusion. Surgical intervention remains the definitive therapy.
Keywords: hemorrhagic pericardial effusion; cardiac tamponade; free wall rupture; aortic dissection; cardiogenic shock; case report